2015
DOI: 10.1007/s00217-015-2442-x
|View full text |Cite
|
Sign up to set email alerts
|

A large diversity of lactic acid bacteria species is involved in the fermentation of wheat used for the manufacture of lemzeiet

Abstract: Algerian couscous named lemzeiet is manufactured from fermented wheat. Historically performedin underground silos called matmor, the fermentation of wheat is now generally carried out in plastic jerrycans withor without addition of vinegar at the beginning of the fermentation. Culture-dependent and culture-independentmethods (PCR-TTGE) were used to characterize lactic acid bacteria and to determine their dynamic and diversity over a two-year period, with and without the addition of vinegar.Fungi, physicochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
(52 reference statements)
2
11
0
Order By: Relevance
“…Our results showed that many strains of pediococci and enterococci seem to dominate the kinetic acidification. This corroborates the previous study on the characterization of the lemzeiet microbiota, where P. pentosaceus and E. faecium were described as dominant from the first stage of the fermentation [17]. L. curvatus (L84), L. brevis (L120), and L. mesenteroides (L70) also showed good acidifying abilities.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our results showed that many strains of pediococci and enterococci seem to dominate the kinetic acidification. This corroborates the previous study on the characterization of the lemzeiet microbiota, where P. pentosaceus and E. faecium were described as dominant from the first stage of the fermentation [17]. L. curvatus (L84), L. brevis (L120), and L. mesenteroides (L70) also showed good acidifying abilities.…”
Section: Discussionsupporting
confidence: 91%
“…have been described by many studies as the best antifungal agents compared to other LAB species [23,46,47]. Moreover, in our precedent study, on lemzeiet, we had highlighted that fermentation process allows the disappearance of fungi flora over time, which reinforces the fact that LAB strains exerted an antifungal activity and make the product safer for consumption [17]. Indeed, LAB are naturally present in many foods and have a long history of safe use in fermentation process [1].…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations